PEMANFAATAN LAPORAN DARI INSTALASI REKAM MEDIS BAGI PENGAMBILAN KEPUTUSAN MANAJEMEN RSU PKU MUHAMMADIYAH BANTUL - , PINTRA FIANA R ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: The medical records used in patient care management, quality review, financial reimbusement, legal affairs, education, research, public health planning and marketing. Surely reports from the medical record installation has important uses for the hospital. Based on initial observations, researchers found that in the RSU PKU Muhammadiyah Bantul have made various types of reports regularly. But the benefits of any report made in the medical record installation for RSU PKU Muhammadiyah Bantul not yet known. Therefore, researchers need to know whether the report made by the medical records official utilized by RSU PKU Muhammadiyah Bantul to make management decisions. Goals: To determine the benefits of a report from the Medical Record Installation for decision making management in RSU PKU Muhammadiyah Bantul. Methods: This type of research is a descriptive study using a qualitative approach with a cross-sectional design. The technique of collecting data using interviews, observation and documentation studies. The subjects were reporting officer and the management of RSU PKU Muhammadiyah Bantul. Object of this study is the report of the Installation Medical Record. Results: Reports made by the reporting officer served in a board meeting in three month period and includes an outpatient clinic patient visits per month grouped by the type of patient is new or old, a number of hospitalizations of patients per ward per month, Hospital Efficiency (BOR, LOS , TOI, BTO, GDR, and NDR), Report on surgery, obstetrics care unit report, 10 Major Diseases (Inpatient, Outpatient, ER, cause of death), patient mortality rate (ER and Inpatient), laboratory examination activities, radiology activities, medical rehabilitation services, prescription writing and services, and number of patient visits per sub districts in Bantul. Medical Record Officer assigned to recapitalize the report of each unit of service to be presented to management. Reports are presented in graphical form as a board meeting, and submitted to management in the form of summary reports in tabular form. The report presented by medical records officers have been able to simplify the management to analyze and make decisions. However, there is still a delay in the presentation of a report due to SIRS is not optimal. And not every unit has a summary report made by medical records officers.